Morbidity and mortality from adenotonsillectomy in children with trisomy 21. (November 2020) - Cottrell, Justin; Zahr, Siraj K.; Propst, Evan J.; Narang, Indra; Amin, Reshma; Chiang, Jackie; Al-Saleh, Suhail; Wolter, Nikolaus E.
Abstract: Objective: Adenotonsillectomy (AT) is common in children with trisomy 21 but outcomes are variable. Therefore, practitioners must have accurate information regarding the risks of the procedure specific to trisomy 21 to help patients weigh the risks and benefits of surgery. The objective of this study was to better characterize morbidity and mortality risk factors from AT in children with trisomy 21. Methods: A single-center retrospective chart review of children with trisomy 21 who underwent AT was conducted from 1992 to 2019. The primary outcome was 30-day post-operative complication rate. Secondary outcomes included intraoperative complications, admission duration, emergency department visits, readmissions, reoperation rate and treatment failures. Results: Two-hundred and fifty one children met study criteria (median age 4.5 years). Seventy-eight patients (31.5%) had a post-operative complication requiring medical intervention, with respiratory issues (42, 53.8%), poor oral intake (29, 37.2%), and bleeding (14, 17.9%) being most common. Postoperatively, 72 patients (28.7%) had a prolonged hospital stay. Sleep disordered breathing (p = 0.003), ASA score >2 (p < 0.001), severe OSA (p = 0.003), preoperative ICU admission (p < 0.001), and aerodigestive comorbidities (p = 0.004) were associated with increased post-operative respiratory complications. No mortalities were identified. Conclusion: This large single institution study evaluating morbidity and mortality following AT in children with trisomy 21 identified a morbidity rate of 31.5%. These findings may improve our ability to anticipate and manage postoperative morbidity in this vulnerable population and facilitate informed discussions with patients and caregivers considering AT.